Effects of acute arm-cranking exercise with electrical muscle stimulation at different intensities on vascular endothelial function - Mizuki Nakamura; Hajime Miura; Ayako Murakami; Yasuaki Tamura (Journal of Physical Fitness and Sports Medicine)
Arm-cranking exercises combined with electrical muscle stimulation (EMS) of the lower limbs at maximum intensity enhance vascular endothelial function. To bring this procedure into clinical application, we examined the effects of acute arm-cranking exercise combined with lower-extremity EMS at different intensities on vascular endothelial function. The study included eight healthy adult males. After resting in the supine position, arm-cranking exercises were performed at an intensity of 50% VO2max for 20 min, and the lower limb received EMS under three trials: maximum intensity trial (A+100%EMS trial), 50% intensity trial (A+50%EMS trial), and 25% intensity trial (A+25%EMS trial). Flow-mediated dilation (FMD), which reflects vascular endothelial function, was measured before and after the procedure, and the normalized FMD (nFMD) was calculated. The mean nFMD before and 30 min after exercise was 0.8 ± 0.3 and 2.3 ± 1.8, respectively, in the A+100%EMS trial and 0.9 ± 0.4 and 1.4 ± 1.0, respectively, in the A+50%EMS trial, indicating a significant increase after exercise under both trials. No changes were observed in the A+25%EMS trial. The combination of arm-cranking exercise and 50% intensity EMS appears to be a clinically applicable program for improving vascular endothelial function, even with reduced exercise intensity.